2001
DOI: 10.1097/00001756-200110080-00029
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific expression of cell cycle inhibitors in the adult brain

Abstract: In the adult brain, neural proliferation is almost absent and neurons are generally not renewed. By contrast, in the olfactory organ, olfactory neurons are produced continuously throughout life. To investigate whether specific cell cycle inhibitors are involved in the control of neural quiescence in adulthood, we compared their expression either in different regions of the adult brain weakly or non neurogenic or, for comparison, in the olfactory mucosa. We show that numerous cell cycle inhibitors are expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…For example, p15 INK4B has been found in the forebrain, p21 has been found in the cerebellum (30,31), and p27 Kip has been found in the cerebellum and postmitotic cortical neurons (31,32). It is likely that other CDK inhibitors also affect neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, p15 INK4B has been found in the forebrain, p21 has been found in the cerebellum (30,31), and p27 Kip has been found in the cerebellum and postmitotic cortical neurons (31,32). It is likely that other CDK inhibitors also affect neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In post-mitotic, terminally differentiated neurons, it is likely that cell cycle activity is arrested by the increased expression of Cdk inhibitors. Numerous cell cycle inhibitors are expressed in the brain either in a ubiquitous fashion (e.g., p19 Ink4d ) or in specific regions: p15 Ink4d in the forebrain; p21 Cip1 in the cerebellum 53 and p27 Kip1 in the cerebellum and cortical postmitotic neurons. 53,54 In animals derived from backcrosses between p27 Kip1 -null and p19 Ink4d -null mice, a subpopulation of neurons showed increased proliferation in the brain, indicating that these two Cdk inhibitors cooperate to maintain differentiated neurons in a quiescent but potentially reversible state.…”
Section: Cell Cycle Related Proteins In Adult Brainmentioning
confidence: 99%
“…Previous studies have suggested that p21 might participate in the establishment of the postmitotic phenotype of neurons (Erhardt and Pittman, 1998;Legrier et al, 2001). Therefore, we examined by immunofluorescence the expression of p21 in Pax6-expressing cells [ The tumor-suppressor p53 gene is involved in cell cycle regulation and differentiation in several biological systems.…”
Section: Pax6 Induces a Postmitotic Phenotypementioning
confidence: 99%